Microbiological and lead contamination of green mussels from Bacoor, Cavite - Carpio, Hazel D.; Rumbaoa, Rowena Grace O. (2001., 2001)
This research deals with the quality assessment of green mussels in Bacoor, Cavite. A survey of the culture sites was done to relate the environmental condition of mussels' habitat to possible contamination of heavy metals and pathogens. Phase I deals with the determination of lead level in green mussels using Flame Atomic Absorption Spectrophotometer. All fresh, boiled and steamed mussel sample exhibited very low lead contents which are below the detection limit of the instrument (<0.002 mg/kg). Phase II, on the other hand, deals with the microbiological examination of fresh and heated green mussels. Total coliform count was used to approximate the total number of coliforms and Salmonella-Shigella agar was employed to detect the presence of Salmonella species. Results obtained from the total plate count ranged from 1.8x104 cfu/ml to 130x 104 cfu/ml. Total coliform count ranged from <1000 cfu/ml to 2.7 x 104 cfu/ml. Salmonella detection showed that the two heat treatments were not sufficient to destroy the pathogen.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Mussels -- Microbiology; Mussels -- Philiipines -- Cavite, Bacoor